A Comparative Study of Playing Patterns on Gambang and Ranat Ek Instruments - Rachman, Abdul; Teangtrong, Pramot; Jirajarupat, Phakamas; Cahyono, Indrawan Nur (Harmonia: Journal of Arts Research and Education, 2021)
Gambang Semarang is one of Indonesia’s traditional music which has an instrument made of wood, namely gambang (xylophone). Thai Pi Phat Ensemble has a Gambang-like instrument called Ranat Ek. In the presentation, each of these instruments certainly has a playing pattern that is characteristic of the music itself. This study aims to identify and describe the pattern of traditional music playing in the Gambang Semarang, especially the Gambang instrument and the traditional music of Thai Pi Phat Ensemble, especially the Ranat Ek instrument. The research method used is qualitative with a musicological approach. Data collection techniques were carried out by using observation, interviews, document studies, and Focused Group Discussions. Data analysis was carried out with the stages of data reduction, data classification, and concluding. The results show that the playing pattern of the Gambang instrument in the Gambang Semarang music contains two types of playing patterns, namely sekaran Nglagu and cengkok ajeg. While the playing pattern of the Ranat Ek instrument in the Pi Phat Ensemble consists of kan ti kro, kan ti kep, kan ti siao mue, kan ti sado, and kan ti sabat. The two instruments have similarities and differences in playing patterns which are most likely due to differences in functions and roles in group play.